Trajectory tracking control of an amphibian robot with operational capability. (30th July 2019) - Yu, Fujie; Chen, Yuan
Although the traditional amphibious robot has the ability of multi-space motion, it has the disadvantage of low power utilization and no operational capability. In order to make it competent in an extremely complex environment, we studied the structural design and control of amphibian robot with operational capability. First, in order to make the robot have the ability of flying in the sky, moving on land, and swimming in the water, a "bevel variant" mechanism for power switching is designed. Then, taking the uncertainty of the kinetic parameters and external influences into account, the kinetic and kinematic models of the system are established. Next, a sliding mode controller that outputs control force for the system and a quadratic calculation optimization algorithm for inverse kinematics solution are designed. Finally, the simulation platform for the system is built based on MATLAB. The simulation results show that when the system is in the land and air flight stages, the vehicle position and orientation tracking error are within ±0.05 m and ±2°, respectively. When the system is in the underwater stage, the end effector position and orientation tracking error are within ±0.15 m and ±3.0°, respectively.